Bio-nano scale modifications of melittin for improving therapeutic efficacy. (3rd July 2022) - Akbarzadeh-Khiavi, Mostafa; Torabi, Mitra; Olfati, Amir-Hossein; Rahbarnia, Leila; Safary, Azam
ABSTRACT: Introduction: Melittin (MLT), a natural membrane-active component, is the most prominent cytolytic peptide from bee venom. Remarkable biological properties of MLT, including anti-inflammatory, antimicrobial, anticancer, anti-protozoan, and antiarthritic activities, make it an up-and-coming therapeutic candidate for a wide variety of human diseases. Therapeutic applications of MLT may be hindered due to low stability, high toxicity, and weak tissue penetration. Different bio-nano scale modifications hold promise for improving its functionality and therapeutic efficacy. Areas covered: In the current review, we aimed to provide a comprehensive insight into strategies used for MLT conjugations and modifications, cellular delivery of modified forms, and their clinical perspectives by reviewing the published literature on PubMed, Scopus, and Google Scholar databases. We also emphasized the MLT structure modifications, mechanism of action, and cellular toxicity. Expert opinion: Developing new analogs and conjugates of MLT as a natural drug with improved functions and fewer side effects is crucial for the clinical translation of this approach worldwide, especially where the chemicals and synthetic drugs are more expensive or unavailable in the healthcare system. MLT-nanoconjugation may be one of the best-optimized strategies for improving peptide delivery, increasing its therapeutic efficacy, and providing minimal nonspecific cellular lytic activity. uf0001